Nonsubstrate based inhibitors of dengue virus serine protease: a molecular docking approach to study binding interactions between protease and inhibitors - Lee, Y.K.; Tan, S.K.; Wahab, H.A.; Yusof, Rohana; Abd Rahman, N. (Malaysian Society for Molecular Biology and Biotechnology, 2007)
The protein-ligand binding interactions studies were carried out by performing dockings of the ligands that were found to be competitively inhibiting the activities of the DEN2 NS2B/NS3 serine protease onto the catalytic triad of a model of DEN2 NS2B/NS3 protease. Results indicate the importance of three out of the five residues reported to be essential for binding activities of the NS2B/NS3 serine protease. These residues are Tyr-150, Asn-152 and Gly-153. In addition, Ser-135 and Gly-151 were also found to be very important in forming hydrogen bonds with the inhibitors. Moreover, Ser-131, Pro-132, Tyr-150 and Asn-152 were found to be important for van der Waals interaction of the ligand, while Val-52, Leu-128, Pro-132 and Val-155 are involved in hydrophobic interaction with the inhibitors.